Efeito do nível de atividade física nas concentrações da ADAM 10 em sujeitos com doença de Alzheimer e saudáveis - Barreto, Maria Carolina [UNESP] (2014)
It is known that physical activity can promote several changes in cognitive functions and today is regarded as a non-pharmacological form of treatment and prevention for Alzheimer's disease. One of the mechanisms that lead to these changes is the production of neurotransmitter uptake and which have a direct action on the central nervous system and, moreover, can be directly related to the modulation and production of biomarkers related to disease. Currently, the main postulates have recommended new diagnostic criteria and research in Alzheimer's disease (AD). Among the various examinations are biomarkers that currently are used solely for the purpose of research, but more and more are gaining space for clinical diagnosis. Among the biomarkers associated with AD there is a catalytic enzyme family of disintegrins and metalopeptidadse, ADAM 10 has among its various functions, the ability to cleave the amyloid precursor protein (APP) and promote the release of a substance and neurogenic neuroprotection to neurons. To elucidate this possible relationship between physical activity and the concentration of that specific enzyme, the study aimed to verify the effect of physical activity at concentrations of enzyme ADAM10 in healthy elderly with AD. The study included 29 healthy and 28 older people with AD. To check the level of physical activity using an accelerometer the elderly and answered the questionnaire Baecke modified for the elderly. In addition, a cognitive function screening test was also applied and evaluated the depressive symptoms of the subjects. By means of a blood collection ADAM10 concentrations are analyzed. Results and Conclusion: It was observed that in both groups the ADAM10 concentrations increased with increasing the physical activity level. There was a significant difference in the average level of physical activity, sedentary behavior, time of moderate / vigorous physical activity, Baeck questionnaire modified for the...